Teraflops from cyberspace. (Economist, 2000)
Discusses distributed computing, a technology emanating from the peer-to-peer computing model. Expectation that distributed computing will be a profitable business model; Details of the technology that breaks down large computations into fragments that can be distributed among computers tied to a network; Power and limitation of the supercomputing technology.